A blastema-predominant canine renal nephroblastoma with gingival metastasis: case report and literature review. (May 2018) - Chen, Bo; Li, Wen-Ta; Wang, Fun-In
Nephroblastomas are uncommon embryonal tumors in dogs. We report herein a blastema-predominant nephroblastoma with gingival metastasis in an 8-y-old Miniature Pinscher dog. Histologically, the mass was composed mainly of blastemal elements with minor epithelial and mesenchymal differentiation. Metastatic masses in the gingiva had histologic and immunohistochemical features similar to those of the primary renal nephroblastoma. Neoplastic cells were extensively positive for both vimentin and PAX8, and scattered positive for cytokeratin. Using the clinical staging of human Wilms tumor, we staged our case as stage IV with <4 mo of survival time. We summarized previous studies of canine renal and spinal nephroblastomas, and analyzed the correlations among clinical staging, histologic classification, and mean survival time of dogs with renal nephroblastomas. Clinical staging was significantly correlated with survival time, as shown in humans. In dogs, however, additional factors can potentially influence the outcome of treatment and disease development.